Diagnostic Potential of Transferrin Glycoforms—A Lectin‐Based Protein Microarray Approach. Issue 5 (13th May 2019) - Penezić, Ana; Križakova, Martina; Miljuš, Goran; Katrlik, Jaroslav; Nedić, Olgica
Abstract : Purpose: Disease or a specific condition may cause alteration of human transferrin (hTf) glycosylation pattern. A specific analytical platform, lectin‐based protein microarray, is designed and optimized for the investigation of hTf glycans, attached to the protein core in their native form. Experimental design: hTf molecules isolated from healthy persons of different age, diabetes mellitus type 2 (T2DM) or colorectal carcinoma (CRC) patients are used for method validation. Reliability of the results is ensured by three criteria for the evaluation of hTf–lectin interactions: i) signal‐to‐noise ratio above 3, ii) signal intensity above 250 arbitrary units, and iii) hTf concentration ensuring high sensitivity of the assay. Results: Six lectins, out of fourteen tested, satisfy the criteria. hTf is spotted at concentration of 50 µg mL −L . When physiological samples (isolated hTf) are analyzed, the highest potential to differentiate between population groups expresses Aleuria aurantia (AAL), Triticum vulgaris (WGA) and Phaseolus vulgaris (PHA‐E) lectins. The initial amount of hTf which can be analyzed is very low (75 pg). Conclusion and clinical relevance: Results confirm that a very sensitive, high‐throughput lectin‐based protein microarray platform can be formulated to detect changes in hTf glycan structures which can be considered as biomarkers of ageing or a disease.